Exploring the Guided Inquiry Learning Model in Biology Practicum: Its Impact on Students' Scientific Attitudes and Cognitive Knowledge - Fetmirwati Fetmirwati; Luiz Gustavo Franco; Maria Theresa G. Tadena (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: The purpose of this study was to determine the differences in scientific attitudes and cognitive knowledge of students between guided inquiry and direct learning models in practical activities by controlling students' prior knowledge. Methodology: This quasi-experimental study employed a Non-Equivalent Pretest-Posttest Control Group Design. From a population of 88 students, 57 were selected using purposive sampling. Instruments included multiple-choice tests and Likert scale observation sheets. Data were analyzed using Microsoft Excel and IBM SPSS 23 with One-Way MANCOVA and Partial Eta Squared for effect size. Main Findings: The guided inquiry learning model is effective in improving students' scientific attitudes and cognitive knowledge. The average scientific attitude of students in the experimental class was 85, compared to 70 in the control class. The average post-test cognitive knowledge score was 75.17 in the experimental class and 50.93 in the control class. The One Way MANCOVA test showed significant differences between groups (p = 0.0001; partial eta squared = 0.840). Partial eta squared is a measure of effect size that indicates the proportion of variance in the dependent variables explained by the independent variable. A value of 0.840 suggests a large effect, meaning the learning model had a strong influence on students’ outcomes. Novelty/Originality of this study: This study integrates guided inquiry learning into food testing on the digestive system topic, uniquely controlling prior knowledge to examine its impact on scientific attitudes and cognitive outcomes, thus enhancing inquiry-based learning insights.